(untitled) (Altre Modernità, 2013)
(Gabriela Wiener, Sexografías, Barcelona, Melusina, 2008, 214 pp. ISBN 978-849-661-453-6) (Gabriela Wiener, Nueve Lunas, Barcelona, Mondadori, 2009, 158 pp. ISBN 978-843-972-203-8)